Study of mast cell and eosinophil count in surgically resected appendix - Priya Priya; Sujata S. Giriyan (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Appendix is a normal true diverticulum of the caecum that is prone to acute and chronic inflammation. Mast cells are present in chronic inflammatory reactions and they secrete cytokines that promote inflammation. Eosinophils are abundant in immune reactions mediated by IgE and in parasitic infection.Objective: To evaluate mast cell and eosinophil count variation in appendicitis and to suggest their possible role in pathogenesis of appendicitis.Materials and Methods: It is a two-year prospective study done on 470 resected specimens of appendices received for histopathology.Results: Mast cells and eosinophils were present in all the appendicular lesions studied. Mean mast cell count was highest in chronic appendicitis and lowest in acute appendicitis. Mucosa of chronic appendicitis showed highest count, lowest was seen in the muscularis propria of acute appendicitis compared to normal / unremarkable appendix taken as controls. Correlation between mast cell density, fibrosis and neural ganglia hypertrophy was seen in chronic appendicitis. Mean eosinophil count was highest in acute suppurative appendicitis and lowest in chronic appendicitis, with highest count in the mucosa of acute suppurative appendicitis and lowest in the muscularis propria of chronic appendicitis.Conclusion: The presence of mast cells and eosinophils in cases of appendicitis supports the allergic theory of appendicitis in which the Type I hypersensitivity reaction leads to recruitment of eosinophils and discharge of primary and secondary mediators of inflammation by degranulation of mast cells which play a role in pathogenesis of appendicitis.